QUEEN MAUD LAND ト ミナミ アフリカ カン ノ ナンキョクヨウ ニオケル エイヨウエン ニツイテ - 塩崎, 愈; シオザキ, マサル; SHIOZAKI, Masaru (国立極地研究所, 1966)
P(論文) The serial observations were carried out along 10°-15° E at every 5° in latitude in JARE-7. In the Antarctic Circumpolar Water, 24 μg-atoms/L of phosphate-P, 100 μg-atoms/L of silicate-Si and 35-38 μg-atoms/L of nitratc-N were observed There was difference between the distribution of phosphate-P and that of silicate-Si, the maximum values of phosphate-P and mtrate-N were observed in 400-600m layer at 60°S, but that of silicate-Si was at a depth of 1,500m Regeneration of phosphate-P and nitrate-N was observed in 400-600m layer in the Antarctic zone and the Antarctic Intermediate Water, and the regeneration of almost all silicate-Si was estimated in the Antarctic zone departmental bulletin paper